Cybertoxicology, molecular docking, and experimental verification reveal the mechanism of action of chlorpyrifos on skin damage - Weibin Du; Wenxiang Zeng; Zhenwei Wang; Huahui Hu; Hongfeng Ruan; Gang Qu (Ecotoxicology and Environmental Safety)
Chlorpyrifos (CPF) is a broad-spectrum organophosphate chloride (OP) insecticide widely used in domestic use and open field. However, there is currently no relevant research revealing the toxic effects of CPF exposure on the skin, then it is necessary to comprehensively understand the toxic effects and mechanisms. The results showed that the skin tissue structure and function of mice were significantly disrupted after CPF exposure. Furthermore, PPI network analysis and molecular docking experiments pinpointed core targets such as Bcl2, EGFR, Caspase-3, TNF-α, IL-1β, and VEGF. Additionally, through KEGG analysis, the VEGF and apoptosis signaling pathways were identified as pivotal pathways implicated in CPF-induced skin toxicity. These core targets and pathways were subsequently confirmed through animal experimentation. In conclusion, our study suggests that CPF exposure primarily induces skin damage by disrupting tissue structure and function, mediated through apoptosis and proliferation processes in skin cells, alongside aberrant angiogenesis and heightened inflammatory response. These insights are expected to advance the development of preventive and therapeutic strategies aimed at mitigating the adverse effects of CPF exposure on the skin.